Comparative Genomics Uncovers the Evolutionary Dynamics of Detoxification and Insecticide Target Genes Across 11 Phlebotomine Sand Flies - Charamis, Jason; Balaska, Sofia; Ioannidis, Panagiotis; Dvořák, Vít; Mavridis, Konstantinos; McDowell, Mary Ann; Pavlidis, Pavlos; Feyereisen, René; Volf, Petr; Vontas, John (Genome biology and evolution, 2024)
Sand flies infect more than 1 million people annually with Leishmania parasites and other bacterial and viral pathogens. Progress in understanding sand fly adaptations to xenobiotics has been hampered by the limited availability of genomic resources. To address this gap, we sequenced, assembled, and annotated the transcriptomes of 11 phlebotomine sand fly species. Subsequently, we leveraged these genomic resources to generate novel evolutionary insights pertaining to their adaptations to xenobiotics, including those contributing to insecticide resistance. Specifically, we annotated over 2,700 sand fly detoxification genes and conducted large-scale phylogenetic comparisons to uncover the evolutionary dynamics of the five major detoxification gene families: cytochrome P450s (CYPs), glutathione-S-transferases (GSTs), UDP-glycosyltransferases (UGTs), carboxyl/cholinesterases (CCEs), and ATP-binding cassette (ABC) transporters. Using this comparative approach, we show that sand flies have evolved diverse CYP and GST gene repertoires, with notable lineage-specific expansions in gene groups evolutionarily related to known xenobiotic metabolizers. Furthermore, we show that sand flies have conserved orthologs of (i) CYP4G genes involved in cuticular hydrocarbon biosynthesis, (ii) ABCB genes involved in xenobiotic toxicity, and (iii) two primary insecticide targets, acetylcholinesterase-1 (Ace1) and voltage gated sodium channel (VGSC). The biological insights and genomic resources produced in this study provide a foundation for generating and testing hypotheses regarding the molecular mechanisms underlying sand fly adaptations to xenobiotics.
Keywords: xenobiotic adaptation; Psychodidae; glutathiontransferasa; cytochrome P450s; Glutathione Transferase; Inactivation, Metabolic; gene family evolution; fylogeneze; xenobiotika; Phylogeny; insekticidy; rezistence k insekticidům; metabolická inaktivace; comparative genomics; molekulární evoluce; Evolution, Molecular; phlebotomine sand flies; Genomics; Insecticide Resistance; systém (enzymů) cytochromů P-450; Animals; Cytochrome P-450 Enzyme System; Xenobiotics; zvířata; Insecticides; genomika